FTIR, XRD, and SEM-EDX Characterization of Synthesized B-Type Carbonated Hydroxyapatite (CHAp) Based on Crab Shells - Muarif, Muhamad Fajar; Yusuf, Yusril; Agipa, Ade Irmadiki (Journal of Energy, Material, and Instrumentation Technology, 2024)
The synthesis and characterization of B-type CHAp based on mangrove crab shells (Scylla serrata) as a source of calcium using the precipitation method has been successfully carried out. Based on the FTIR results, the substitution of carbonate ion for phosphate, which indicates the formation of B-type CHAp, is characterized by the appearance of absorption at wave numbers (CO32-) 1426 and 875 cm-1, PO43- at wave numbers 965, 619 & 569 cm-1. The XRD results show that diffraction peaks (211), (300), and (202) appear at an angle of 2θ ranging from 31°-34°, and there is a phenomenon of a-axis contraction and c-axis expansion in the HAp lattice structure. The SEM-EDX results show that the Ca/P ratio is 1.72, and the carbonate content is 5.01 wt%. All of these parameters are characteristics of CHAp, so it can be concluded that type-B CHAp has been formed.